A High Performing Group: Relationship between Group Cohesiveness and Work Performance: A Conceptual Study - Rahman, Reezlin; Abdullah, Najmiah; Awang, Zurina (Archives of Business Research, 2019)
Working in groups generates more diversity output. A successful organizations usually have a high-performance teams to work together. High-performing teams comprise of structured members who are always aware and ready in every job task. In fact, a minimum supervision can be implemented to this team in order to achieve the organization objectives. One of the criteria that contributes to a high performing team is the group cohesiveness. The cohesiveness of the group will make the group members always united and prioritize the group in an effort to complete a job task. Not exaggerate that, each member of the group will do whatever it takes to achieve the final goal of the group. Among the factors that lead to group cohesiveness are through communication, understandable objectives and group member’s commitment. To ensure the cohesiveness of the group continues, the management should set the organizational goals, provide a conducive working environment, setting clear the goal, expectations and responsibilities, provide appropriate training and staffing and also empower them to act. In a simple understanding, the higher the cohesion in a group, the greater the performance of the work in an organization. Keywords: High Performance Group, Cohesiveness, Job Performance